PENGARUH TOTALITAS KERJA DAN MODAL PSIKOLOGIS TERHADAP KEPUASAN KERJA DRIVER GOJEK DI JAKARTA SELATAN - Ardisa Citradewi; J. P. Soebandono (‎‎‎TAZKIYA Journal of Psychology, 2017)
This study aims to determine the effect of the work engagament and psychological capital to job satisfaction drivers gojek. Through this research is expected to find out how far the influence of the totality of work and psychological capital on the drivers of gojek. This research uses quantitative approach with regression analysis method, and validation test of construct using Confirmation Factor (CFA) technique. The sample numbered 175 drivers gojek. The sample of research was determined by using non probability sampling technique. The data collection instrument using Job Satisfaction Survey (JSS) developed by Spector, Utrecht Work Engagement Scale (UWES) was developed by Schaufeli and Bakker and Psychological Capital Questionner (PCQ-24) developed by Luthans, Avolio, et al., 2007. The results of this study indicate that there is a significant influence of the variable influence of work engagement and psychological capital with a significance value of 0.000 or p <0.05 to job satisfaction. So the nil hypothesis (Ho) that exist in the major hypothesis in this study was rejected. The result of the test of the minor hypothesis examining the influence of 7 IV, there are two nil hypothesis (Ho) rejected, it means that there are two IV that have significant effect on job satisfaction, the absorption and resilience variable, while the vigor variable, dedication, self efficacy, optimism and hope effect on job satisfaction. DOI:10.15408/tazkiya.v22i2.8405